An Analysis on The Concept Comprehension Skill Through the Two-Tier Multiple Choice in Online Assessment - Yuni Pantiwati; Wahyu Prihanta; Endrik Nurrohman (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
The corona virus outbreak has an impact on learning activities. Indonesia establishes online or online learning so that learning activities continue and are safe. Assessment and evaluation must continue to be carried out. One way of assessing authenticity can be using Two Tier Multiple Choice (TTMC). This study aimed to analyze the ability to understand the concept of Biology education students through Two-Tier Multiple Choice in online assessment. This type of research is descriptive qualitative. The research was conducted for one semester. The research subjects were semester 3 students who program and attend lectures on Media and Learning Resources at the Biology Education Study Program, FKIP-UMM. The academic year 2020/2021. The number of students is 85 people. The sampling technique used is the saturation sampling. The data were collected utilizing a multiple-choice test in the form of TTMC. Aspects that are measured include aspects of understanding and analyzing. The qualitative descriptive analysis was conducted to classify the data collection. The result showed that 37.6% of students entered the criteria for learning outcomes under the minimum standard mastery (MSM), 31.7% were according to the MSM standards, and 30.6% were in the criteria above the MSM. In the aspect of understanding (C2), 63.5% of students can answer questions correctly, and 36.5% of students have not answered correctly, in the aspect of analyzing (C4), as many as 41.4% of students can answer questions correctly and 58.6% of students not correct in answering the questions of the total evaluated student population.